Anthelmintic resistance, husbandry practices and plant remedies for control of gastrointestinal strongyles in goat farms in Kelantan, Malaysia - Hassan Basri, Basripuzi Nurul Hayyan (2013)
Gastrointestinal parasitism is an important disease in small ruminants that relies largely on chemotherapeutic control approach. Nevertheless development of anthelmintic resistance urges the need to investigate non-chemical control approaches. A questionnaire survey on husbandry practices was conducted in eight farms in Pasir Mas and Kota Bharu, Kelantan where 202 goats were screened for gastrointestinal strongyles. Based on presence of the parasites, a total of 161 goats were selected for this study. The significant (p <0.05) effects of husbandry practices on faecal egg count (FEC) was found with the time of cutting grasses, type of grasses fed, use of local plant-based dewormer, use of anthelmintics and use of goat manure as fertiliser. However when the other practices remained constant, only the use of anthelmintics and local plant-based dewormer were found to have significant (p < 0.01) effects on worm burden as analysed by independent t-test and analysis of variance. This study was followed by Faecal Egg Count Reduction Test (FECRT) using albendazole, ivermectin, levamisole and closantel. The goats were divided into control and treatment groups of at least five animals per group. The arithmetic mean of post-treatment FEC of the control and treated groups were analysed and varying levels of resistance were detected to albendazole, ivermectin, levamisole and closantel in six, five, two and two goat farms respectively. Resistance was suspected against albendazole, ivermectin and levamisole in one farm. Strongyle populations in two farms were still susceptible to levamisole while those in one farm was susceptible to albendazole. Levamisole was found to be the most effective anthelmintic in this study. The questionnaire revealed that some goat farmers in Kelantan used local plants as dewormer to treat their herds. This practice evoked interest as a potential non-chemical control approach. In the present study, enhanced virgin coconut oil (EVCO) and senduduk (Melastoma malabathricum) were evaluated for their anthelmintic properties. 10% EVCO dissolved in 90% virgin coconut oil and 10% EVCO dissolved in 90% palm oil were given orally to two groups of goats. The efficacy test indicated that EVCO was insufficiently active as an anthelmintic. In vitro test compared the larvicidal effect of 1.25, 2.5, 5 and 10 mg ml-1 of senduduk solution while in vivo efficacy test was conducted by comparing FEC of the control, levamisole and senduduk treated groups. Senduduk was found to be ineffective as a larvicide as well as an anthelmintic. The questionnaire also revealed that some farmers recycled goat manure as fertiliser which may become the source of infection. Hence presence of free-living stages particularly the infective larvae in manure needs to be determined. Goat faeces containing strongyle eggs were deposited into five heaps representing five replicates for daily sampling and subjected to FEC, larvae identification and enumeration over 23 days of study. Infective larvae counts consisted of Haemonchus contortus, Trichostrongylus sp. and Oesophagostomum sp. reached a peak on Day 8 and were negligible by Day 14 when the manure was safe to be used as fertiliser for grasses meant for animal feed. As a conclusion, resistance of caprine gastrointestinal strongyles to different anthelmintic classes in Kelantan has become critical. Caution must be taken as resistance may develop to levamisole, the only current effective anthelmintic. Thus combination of the effective anthelmintic and sustainable husbandry practices may be implemented to control gastrointestinal strongyles in small ruminants. Additionally, local plants claimed by farmers to have deworming effects should be investigated as one of the non-chemical control options.